Cultivo do algodoeiro irrigado com águas salinas de acordo com a fase de desenvolvimento da cultura - Mota, Andygley Fernandes (2014)
Over the past 10 years, Brazil went from importer to exporter of cotton, ranking fifth among the countries that produce cotton in the world, accounting for 5.7% of world production. Water quality is one of the factors that cause negative effects on crop growth and affect production. The present study aimed to evaluate the influence of irrigation with saline water on growth, nutrition, production and fiber quality colored cotton (green BRS), plus some soil chemical properties. The study was conducted under field conditions at the Experimental Farm Rafael Fernandes, owned by the Universidade Federal Rural do Semi-Árido - UFERSA. The experimental design was randomized blocks with six treatments and five repetitions, the treatments consisted of six combinations of three waters, with distinct, alternating during the stages of crop development levels of salinity (S). The water used in irrigation salinity S1 was drawn from a well Acu Sandstone aquifer at an average depth of 1000 m. The water salinity S3 was prepared by adding, in the S1 water, salt to submit a level approximate salinity of most water sources Jandaíra Limestone aquifer. The water salinity S2 obtained by mixing equal volumes of water S1 and S3, and the Electrical conductivities, 0.55, 2.16 and 3.53 dS m-1, respectively, the three waters. The green cultivar BRS was reduced in their growth parameters, but production did not differ between treatments. Still use high water salinity (3.5 dS m-1) throughout the crop cycle may be feasible, according to the conditions of the study. The use of lower quality water can be an alternative for producers, enabling a reduction in the consumption of water of better quality